The Beveridge-Nelson decomposition of economic time series: some observations on four ASEAN countries - Hamizun Ismail , (Penerbit ukm, 2008)

(untitled)
The primary objective of this study is to experiment with a procedure in implementing the Beveridge-Nelson decomposition. In particular, we apply the Arino-Newbold procedure to obtain the transitory components of several economic aggregates of four ASEAN countries, namely Indonesia, Malaysia, Thailand and Singapore. The results are then compared with some stylized facts about these variables. On the overall, the technique produces consistent results